The Strengths and Difficulties Questionnaire overseas: Evaluations and applications of the SDQ beyond Europe - Woerner, W.; Fleitlich-Bilyk, B.; Martinussen, R.; Fletcher, J.; Cucchiaro, G.; Dalgalarrondo, P.; Lui, M.; Tannock, R. (Dr Dietrich Steinkopff Verlag, 2004)
Background During the few years that have passed since it became available, the Strengths and Difficulties Questionnaire (SDQ) has been extensively evaluated and widely applied to assess behaviour disorders of children and adolescents in European countries. In contrast, relatively few reports have published SDQ results obtained in other parts of the world, although its briefness and availability in over 40 languages make this instrument particularly attractive for international collaborations and cross-cultural comparisons concerning clinical and epidemiological issues. Objectives This initial overview summarises some of these non-European experiences with the SDQ by presenting a selection of projects that have either psychometrically evaluated this novel questionnaire, applied it to screen for behaviour disorders, or employed its parent-, teacher- or self-rated versions as research tools. Since a large part of the mentioned studies are ongoing or have only recently been completed, much of the work reported here is still unpublished. Conclusions Across a huge variety of cultures and languages, experience gained with the SDQ in other continents has supported European evidence of good psychometric properties and clinical utility of this questionnaire. Since worldwide usage of the SDQ can be expected to increase in the future, more international coordination is encouraged, in order to fully exploit the promising potentials of this versatile assessment tool and systematically investigate cross-cultural differences and similarities in child and adolescent behaviour.
Keywords: Strengths and Difficulties Questionnaire (SDQ); cross-cultural comparisons; screening instrument